Variation in Plant Morphology and Sinigrin Content in Ethiopian Mustard (Brassica carinata L.) - Tesfay Teklehaymanot; Haijing Wang; Jianli Liang; Jian Wu; Runmao Lin; Zhen Zhou; Xu Cai; Xiaowu Wang (Horticultural Plant Journal, 2019)
Ethiopian mustard (Brassica carinata) is mainly grown as a leafy vegetable and oilseed crop. Sinigrin is predominant glucosinolate in the leaves of Ethiopian mustard. It is hydrolyzed by enzyme myrosinase to produce bioactive product specifically allyl-isothiocyanates. Due to sinigrin content, Ethiopian mustard has a mild flavor and it is a healthy addition to human diet. However, sinigrin concentration depends on genotype. Understanding variations of plant morphology and sinigrin content may be the first step for crop improvement. According to the analyses of various plant characteristics among ninety nine Ethiopian mustard accessions, we found significant differences in plant height, chlorophyll content, and petiole length. In addition, sinigrin content was determined using ultra-performance liquid chromatography tandem quadrupole mass spectrometers/tunable ultraviolet detector (UPLC-TQS/TUV). We found a significant difference in sinigrin content among leaves of 94 Ethiopian mustard accessions. Except for petiole length, the sinigrin content was negatively correlated with leaf area, leaf width, number of primary branches, and plant height. This information will help Ethiopian mustard breeders in screening breeding lines for new accessions. Keywords: Brassicaceae, mustard, sinigrin, leafy vegetable, glucosinolate, metabolite